SIKAP KEBERAGAMAAN HMI DALAM KEMAJEMUKAN ORANG BASUDARA (STUDI TENTANG SEJARAH PERJALANAN HMI DI AMBON) - M. Syafin Soulisa (DIALEKTIKA, 2018)
This paper aims to determine the attitude of religiosity in the lives of Orang Basudara. HMI organizationally is a part of Indonesian history always brought peace to overcome suffering together in accordance with the lofty ideals of the Indonesian people as a form of moral responsibility on the order of Indonesian people, especially Orang Basudara which of course starts from himself. It is important for HMI to find the religious identity in the spirit of nationality to spiritual-Indonesia's pluralist. In analyzing the data, the author uses the historical method with qualitative approaches, analytical techniques which use is descriptive. Based on the results of the study concluded that the HMI trip along Orang Basudara since 1957 and has been realizing an inclusive religious attitude and partiality to the unity and togetherness with Orang Basudara. It is not to undermine its identity, but enrich the existence of humanity by accepting and understanding the cultural and religious characteristics that exist